Social adaptation of Kazakh nomads in the period of forced collectivization - Bakyt Zh. AtantaevaKuralay R. Zhirindinova, Аlbina S. Zhanbosinova, (Opción, 2019)
The objective of the study is to identify and make a system analysis of adaptation practices of Kazakh nomads during forced collectivization. The methodological framework of the study is Ralph Dahrendorf’s conflict theory that provides insight into the social stratification theory and social order. The present theme-focused research study shows that, in the context of forced collectivization, the authorities channeled their efforts, both at the central and regional levels, into eliminating social patrimonial communicative indicators. In conclusion, Analysis of forced collectivization methods that led to malfunctions in the political and economic systems influenced the content of Kazakh population’s behavioral motives.